Case Report: Concurrent esophageal and spinal cord compression in cervical spondylosis: integrated anterior osteophytectomy and zero-profile ACDF for dual pathology decompression - Wu, Jian; Shao, Wei; Zhu, Wenqing; Mo, Jianwen (Frontiers in Surgery, 2025)
Cervical spondylotic dysphagia (CSD) and cervical spondylotic myelopathy (CSM) represent two distinct clinical entities within degenerative cervical pathology. Their co-occurrence creates diagnostic and therapeutic dilemmas due to overlapping pathophysiological mechanisms. CSD primarily stems from anterior cervical osteophytes mechanically compressing the esophageal lumen, resulting in progressive dysphagia and pharyngeal discomfort. Conversely, CSM develops through spinal cord compression mediated by posterior osteophytic growth, intervertebral disc herniation, or ossification of the posterior longitudinal ligament (OPLL), clinically manifesting as limb paresthesia, motor weakness, gait instability, and impaired manual dexterity. We describe a 58-year-old male presenting with progressive dysphagia accompanied by bilateral lower extremity weakness. Radiological evaluation demonstrated prominent anterior osteophytes with bridging syndesmophytes at C4–C6 levels causing posterior pharyngeal wall displacement, concurrent with C3–C7 OPLL and multilevel disc herniations inducing spinal cord compression. Surgical management comprised anterior cervical osteophytectomy via a standard Smith-Robinson approach, followed by two-level anterior cervical discectomy and fusion (ACDF) utilizing a zero-profile interbody cage system, achieving dual objectives of spinal canal decompression and segmental stabilization. The patient exhibited complete dysphagia resolution and substantial neurological recovery during postoperative follow-up.